PENGARUH DEVIDEN PER SHARE, NET PROFIT MARGIN DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016 - Ros Nida Siregar (Jurnal Education and Development, 2019)
Investors investing in companies that have a good enough profit because it showed good prospect, so investors are keen to invenst which would influence the company share price. One way to predict stock price isto do fundamendal analysis through financial ratios. Financial ratios can be used by investors as tool to nalyze the company’s capability in generating profit based on share owned. This shows that financial ratio is useful in assessing the financial condition of the company. The company’s stock value is reflected in the performance of the company, if the company’s financial performance shows that there is a good prospect then shares will be sought after by investors and the price will increase. This indicates the existence of a positive relationship between the financial performance by its stock price. The ratio that can be used by investors, among othes Devidend Per Share (DPS) Net Profit Margin (NPM) and Return On Equity (ROE). This study aims to determine the effect of DPS, NPM and ROE on stock prices in the Company Manufacture Sector listed on the Indonesia Stock Exchange period 2014-2016.The research approach used in this research is associative and descriptive method to know or no influece from dependent variable againts the independent variable. Sampling technique used in this research, is non probability sampling by using purposive sampling method, that is sample determination technique with certain consideration. The number of study population is 132 companies while the sample number that entered the sampling criteria is 68Manufacture company listed in Indonesia Stock Exchange during 2014-2016. Statistical analysis used in this research is classical assumption test, hypothesis test by using t test and F test and coefficient of determination analysis. The result of this research showed that Devidend Per Share (DPS) Net Profit Margin (NPM) and Return On Equity (ROE) amounted to 0.9446 or influential 94.46% againts the price of the stock on the company’s sector of manufacture. Listed on The Indonesia Stock Exchange of the period 2014-2016. While partially only DPS and ROE have a positive and significant effect on stock prices ie the proportion of respectively 8.98% and 1.64%. While NPM does not have a significant influence on stock prices.